Turcot's syndrome presenting as an acute abdomen - Saleh Busbait; Abdullah Al-Babtain; Yaser Tawfeeq; Yasser AlJehani; Hussah Al-Buainain (Elsevier, 2019)
Turcot syndrome is a rare hereditary syndrome characterized with the clinical association of colorectal polyposis and brain tumors. Usually the time interval between either the colorectal polyposis or brain tumors presentation is about 5 years in most situation. Colorectal cancer is one of the most common cancer in adult, however it is rare to be seen before the age of 20 years, with annual incidence of 1-2 per million in the US, colorectal cancer associated with a predisposing syndrome account for about 3-4%. We report a rare case of Turcot Syndrome presenting with acute abdomen due to complicated adenocarcinomas involving the transverse colon, sigmoid and rectum in 17-year-old patient who had Glioblastoma 13 years prior to it suggesting Turcot Syndrome. Keywords: Turcot syndrome, Polyposis, Adenocarcinoma, Glioma, Pilomatrixoma